Postcoital Bleeding: A Review on Etiology, Diagnosis, and Management - Christopher M. Tarney; Jasmine Han (Obstetrics and Gynecology International)
Postcoital bleeding refers to spotting or bleeding that occurs after intercourse and is not related to menstruation. The prevalence of postcoital bleeding ranges from 0.7 to 9.0 percent of menstruating women. There are multiple etiologies for this common complaint in which most are benign such as cervicitis or cervical polyps. However, the most serious cause of postcoital bleeding is cervical cancer. There are currently no recommendations from governing bodies such as the American College of Obstetricians and Gynecologists on evaluating and treating women with postcoital bleeding. The purpose of this paper is to discuss the common causes of postcoital bleeding, the etiologies of postcoital bleeding, and the likelihood that malignancy is the underlying cause. After an extensive literature review, we compiled a paper illustrating the key concepts a practitioner should know when it comes to postcoital bleeding. Finally, this review will conclude with treatment options for women who are found to have an identifiable source for their bleeding and a discussion on the natural history of postcoital bleeding in women who are found to have no identifiable etiology on evaluation.